Simple polynomial division

Algebra Level 1

Find the remainder when x 3 + 4 x 2 5 x + 3 x^{3} + 4x^{2} - 5x + 3 is divided by x 2 x-2 .


The answer is 17.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Jack Rawlin
Dec 22, 2014

Let f ( x ) = x 3 + 4 x 2 5 x + 3 f(x) = x^3 + 4x^2 - 5x + 3 and r = R e m a i n d e r r = Remainder

x 2 = 0 x = 2 x - 2 = 0 \Rightarrow x = 2

Due to the remainder theorem f ( x ) = r f(x) = r so when x = 2 x = 2

f ( 2 ) = r f(2) = r

Substituting f ( x ) = x 3 + 4 x 2 5 x + 3 f(x) = x^3 + 4x^2 - 5x + 3 gives us

( 2 ) 3 + 4 ( 2 ) 2 5 ( 2 ) + 3 = r (2)^3 + 4(2)^2 - 5(2) + 3 = r

This expands out into

8 + 16 10 + 3 = r 8 + 16 - 10 + 3 = r

Evaluating this (using Bidmas of course) gives us

17 = r 17 = r

So the remainder is 17 17

Drex Beckman
Jan 12, 2016

You can use synthetic division: Pardon my poor illustration, I can't figure out how to do this in latex: x 2 x-2 becomes 2 and x 3 + 4 x 2 5 x + 3 x^{3}+4x^{2}-5x+3 becomes 1 4 -5 3.

Therefore, our answer is 17 \boxed{17}

x^3 + 4x^2 - 5x + 3 ÷ x-2 can be written as an identity as this form:

x^3 + 4x^2 - 5x + 3 = (x-2)(ax^2 + bx +c) +d (d being the remainder )

We can expand the second side out to get ax^3 + (b-2a)x^2 + (c-2b)x -2c +d

We can replace those values with the original equation so a=1, b-2a =4, c-2b=-5, -2c+d=3

We can rearrange and solve those to get a=1, b=6, c=7 and d=17, and since d is the remainder , the answer is 17

Justin Tuazon
Nov 29, 2014

L e t P ( x ) = x 3 + 4 x 2 5 x + 3 T h e R e m a i n d e r T h e o r e m s t a t e s t h a t t h e r e m a i n d e r w h e n P ( x ) i s d i v i d e d b y x a i s P ( a ) U s i n g t h e r e m a i n d e r t h e o r e m , T h e r e m a i n d e r w h e n d i v i d i n g P ( x ) b y x 2 i s P ( 2 ) = 8 + 16 10 + 3 = 24 7 = 17 P ( 2 ) = 17 Let\quad P(x)={ x }^{ 3 }+4{ x }^{ 2 }-5x+3\\ \\ The\quad Remainder\quad Theorem\quad states\quad that\\ the\quad remainder\quad when\quad P(x)\quad is\quad divided\quad by\quad x-a\\ is\quad P(a)\\ \\ Using\quad the\quad remainder\quad theorem,\\ The\quad remainder\quad when\quad dividing\quad P(x)\quad by\quad x-2\quad is\\ P(2)=8+16-10+3=24-7=17\\ \\ \qquad \qquad \qquad \qquad \boxed { P(2)=17 } \\ \\ \\

Anil Gupta
Nov 21, 2014

put x-2=0 or x=2 in given equation x^3 + 4 x^2 -5 x +3 and we get 17 that will be the reminder

I believe you are using the remainder theorem. Let me help you organise your solution.

P ( x ) = x 3 + 4 x 2 5 x + 3 P(x) = x^{3} + 4x^{2} -5x + 3

By Remainder Theorem,

P ( 2 ) = 8 + 4 ( 2 ) 2 5 ( 2 ) + 3 = 17 P(2) = 8 + 4(2)^{2} - 5(2) + 3 = 17

Tan Yong Boon - 6 years, 6 months ago

Log in to reply

Boon how you know

Srivathsan Veeramani - 6 years, 6 months ago

Log in to reply

boon what is mod i dont really understand its purpose

Srivathsan Veeramani - 6 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...